Comparison of Clinical Outcomes Between Chinese Patients Receiving Hepatectomy With or Without Enhanced Recovery After Surgery Strategy - Kang, Tieli; Jia, Zhishuo; Xing, Guoquan; Zhou, Quanhe (Frontiers in Surgery, 2021)
Purposes: As the first time in the China, the current study was designed to compare the clinical outcomes between Chinese patients receiving hepatectomy with and without enhanced recovery after surgery (ERAS) strategy. Methods: The current study enrolled 250 patients who would receive hepatectomy. Patients were randomized into two groups: ERAS group (n=125, ERAS strategy) and control (n=125, conventional care). Mortality, length of hospital stay, readmission and complications were assessed during 30 days after operation. Results: Age of whole cohort was 65(63-68) years with 152 males (60.8%). There was no difference between two groups in baseline features, such as age, sex, medical history, Child–Pugh hepatic function, American Society of Anesthesiologists physical status, operative type, hepatectomy type and hepatic pathology (P>0.05 for all). There was no occurrence of death in two groups. Patients in ERAS group had significantly less occurrence of postoperative complications and shorter length of hospital stay (P<0.05 for all). Deep vein thrombosis occurred in 7 patients in control group, but did not occurred in ERAS group (P<0.05). Patients in two groups had similar occurrence of readmission (P>0.05). Conclusions: ERAS strategy significantly decreased the occurrence of operative complications and shortened the length of hospital stay without any increase in the mortality or readmission in Chinese patients receiving hepatectomy.